2015
DOI: 10.1584/jpestics.d14-083
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, gibberellin production and sensitivity to ipconazole of the <i>Fusarium fujikuroi</i> species complex isolates obtained before and after its launch

Abstract: Sensitivities to ipconazole of 50 isolates of the Fusarium (Gibberella) fujikuroi species complex (Ff complex) obtained from rice in Japan before 1994 (group A: before the launch of ipconazole) and 65 isolates after 1994 (group B) were investigated. Most isolates were identified as Fusarium fujikuroi, while 5 isolates in group A and 4 isolates in group B were identified as Fusarium proliferatum with species diagnostic PCR-RFLPs. The minimum inhibitory concentration (MIC) range, profiles in sensitivity to ipcon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In our previous study, seed treatment with ipconazole at the commercial dosage showed high efficacy against all pathogenic (GA producer) F. fujikuroi isolates. 9,10) In GA producers with higher sensitivity (MIC less than 1.25 mg/L in PD liquid medium and less than 1.56 on PDA), the expression level of CYP51 did not tend to increase MIC dependently, and no substitution in the amino acid sequence of CYP51 protein in F. fujikuroi isolates may support the stable high efficacy of ipconazole against rice Bakanae disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, seed treatment with ipconazole at the commercial dosage showed high efficacy against all pathogenic (GA producer) F. fujikuroi isolates. 9,10) In GA producers with higher sensitivity (MIC less than 1.25 mg/L in PD liquid medium and less than 1.56 on PDA), the expression level of CYP51 did not tend to increase MIC dependently, and no substitution in the amino acid sequence of CYP51 protein in F. fujikuroi isolates may support the stable high efficacy of ipconazole against rice Bakanae disease.…”
Section: Discussionmentioning
confidence: 99%
“…GA productivity was detected in the F. fujikuroi isolates with higher sensitivity to ipconazole but not in the isolates with lower sensitivity and F. proliferatum. 10) CYP51 belongs to the family of cytochrome P-450, which catalyzes 14α-demethylation of 24-methylene-dihydro-lanosterol in fungal ergosterol biosynthesis pathway, and it is the target enzyme of DMI fungicides. Many papers describe the sensitivity mechanisms of plant pathogenic fungi to DMI fungicides including the mutation of CYP51, but only a few are concerned with Fusaria.…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal efficacy of triazole has been assessed to control F. moniliforme by using 25% tebuconazole emulsifiable concentrate (EC), 25% propiconazole EC, and 2.5% difenoconazole EC (Hossain K. S. et al, 2015 ). Application of triazole fungicides such as propiconazole (Bagga and Sharma, 2006 ) and ipconazole (Tateishi and Suga, 2015 ; Li et al, 2018 ) and imidazole fungicide such as prochloraz (Kumar et al, 2020 ) significantly suppressed F. fujikuroi growth. Soaking of rice seeds for 24 h in a diluted solution of 200-folds of ipconazole wettable powder at 6% or ipconazole at 0.0472 μg/mL showed efficacy against bakanae disease.…”
Section: Control Methodsmentioning
confidence: 99%
“…Thus, F. fujikuroi , the only Fusarium species capable of GA3 synthesis, by regulation and expression of jasmonic acid-responsive gene and jasmonic acid-mediated plant immune responses [ 55 , 56 ]. Furthermore, production of GA was also linked with the fungicide sensitivity of different F. fujikuroi isolates [ 57 , 58 ].…”
Section: Symptoms and Secondary Metabolitesmentioning
confidence: 99%